Analysis of the Subsidized Mortgage Program for High-Income Communities Low at Bank Syariah Indonesia KCP Surabaya Manukan - Maulida Vina Alfansyah; Muhammad Syauqi (LP2M IAIN Palopo, 2026)
This study aim for analyze implementation of the credit program Subsidized Home Ownership (KPR) for the community earning low at Bank Syariah Indonesia (BSI) KCP Surabaya Manukan. Research This focused on the program implementation process, the benefits obtained customers, as well as obstacles faced​ in implementation financing House subsidy Sharia- based research use approach descriptive qualitative. Subject study consists of on account officers, financing marketing, and customers recipient selected subsidized mortgage financing​ use the study used purposive sampling technique. Data collection techniques were conducted through semi-structured interviews, observation, and documentation. The data obtained were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the subsidized mortgage program at BSI KCP Surabaya Manukan has been carried out systematically through the stages of customer education, document verification, field surveys, and murabahah contracts. The program has had a positive impact on low-income communities, especially in increasing access to affordable housing ownership, creating family economic stability, and improving community welfare. However, the program implementation still faces several obstacles, such as low public literacy regarding sharia financing, customer income instability, incomplete administrative documents, and limited availability of subsidized housing units. This study implies that the success of the sharia subsidized mortgage program requires stronger synergy between banks, developers, and the government, as well as increased public education regarding sharia financing products. Future research is recommended to expand the research location and use a mixed methods approach to obtain more comprehensive results regarding the effectiveness of the sharia subsidized housing financing program in Indonesia.